Peranan Strategis Internet Dalam Pemasaran Global - Haliza, Nurul; Munawwarah, Sy Haura; Nazara, Bobby Sapriman; Suhairi, Suhairi (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
The internet is not only a promotional tool, but also plays a key role in facilitating global distribution, cross-border communication, and in-depth data analysis. With its ability to reach consumers around the world through websites, social media and e-commerce platforms, the internet creates global connectivity that allows companies to capitalize on opportunities in international markets quickly and efficiently. The use of the internet is also shaping a new paradigm in customer interaction, enabling deep direct and real-time engagement between companies and consumers across different walks of life. This research was conducted using qualitative techniques. Through a qualitative approach, data is collected through literature studies and document analysis relevant to the theme of this research. The purpose of this work is to illustrate how the strategic role of the internet in global marketing not only changes the way businesses communicate, but also leads to strategic innovations to optimize brand presence, overcome cross-border challenges, and achieve success in an increasingly integrated global market.